Production of polymer compositions using lignin-based fillers
The lignin-based filler prepared by hydrothermal carbonization is used to produce polymer compositions, which solves the need for sustainable black fillers, realizes black polymer compositions without additional colorants, and improves sustainability and biocarbon content.
Patent Information
- Application Number
- CN202380097308.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-11-14
AI Technical Summary
Existing technologies struggle to provide sustainable, renewable black coloring fillers or pigments, and the use of carbon black has environmental impacts, necessitating the search for alternative materials to reduce emissions.
It is prepared by hydrothermal carbonization using lignin-based fillers and is used to produce polymer compositions. The color is represented by L, a, and b values, and no additional colorant is required.
This enables the production of black polymer compositions using renewable materials, reducing environmental impact and improving the sustainability and biocarbon content of the polymer compositions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This disclosure relates to the use of lignin-based fillers in the production of polymer compositions. This disclosure also relates to the use of the produced polymer compositions in packaging, automotive, construction, agricultural, and / or electronic applications. This disclosure further relates to the use of the produced polymer compositions in tires, tire treads, tire sidewalls, cable sheaths, hoses, drive belts, conveyor belts, roller covers, shoe soles, shock absorbers, seals, profiles, and / or damping elements. Furthermore, this disclosure relates to a polymer composition. Background of the Invention
[0003] Carbon black is commonly used as a pigment or filler in black plastics. The sustainability of plastic manufacturing components is crucial, necessitating bio-based and renewable parts. Therefore, the inventors recognized the need to continuously seek sustainable solutions to produce renewable black coloring fillers or pigments for various applications, while reducing emissions. Summary of the Invention
[0004] The use of a lignin-based filler in the production of a polymer composition is disclosed. The color of the filler is represented by an L value of 25–50, an a value of 7–15, and a b value of 11–22. The color of the polymer composition is represented by an L value of up to 22, an a value of up to 7, and a b value of up to 9. The amount of the lignin-based filler used is 0.5–50% by weight, based on the total weight of the polymer composition. The lignin-based filler is prepared by hydrothermal carbonization of lignin.
[0005] The use of polymer compositions produced for the purposes defined in this specification is also disclosed in packaging, automotive, construction, agricultural and / or electronic applications.
[0006] The use of the polymer compositions produced is also disclosed in tires, tire treads, tire sidewalls, cable sheaths, hoses, drive belts, conveyor belts, roller covers, shoe soles, shock absorbers, seals, profiles and / or damping elements.
[0007] A polymer composition is also disclosed, the color of which is represented by an L value of up to 22, an a value of up to 7, and a b value of up to 9, wherein the polymer composition is obtained by combining a lignin-based filler with the polymer, the color of which is represented by an L value of 25-50, an a value of 7-15, and a b value of 11-22, wherein the polymer composition contains 0.5-50% by weight of lignin-based filler based on the total weight of the polymer composition, and the lignin-based filler is prepared by hydrothermal carbonization of lignin. Detailed Implementation
[0008] The use of a lignin-based filler in the production of a polymer composition is disclosed, wherein the color of the filler is represented by an L value of 25–50, an a value of 7–15, and a b value of 11–22, and the color of the polymer composition is represented by an L value of up to 22, an a value of up to 7, and a b value of up to 9, wherein the amount of the lignin-based filler is 0.5–50% by weight based on the total weight of the polymer composition, and wherein the lignin-based filler is prepared by hydrothermal carbonization of lignin.
[0009] The use of polymer compositions produced for the purposes defined in this specification is also disclosed in packaging, automotive, construction, agricultural and / or electronic applications.
[0010] The use of the polymer compositions produced is also disclosed in tires, tire treads, tire sidewalls, cable sheaths, hoses, drive belts, conveyor belts, roller covers, shoe soles, shock absorbers, seals, profiles and / or damping elements.
[0011] A polymer composition is also disclosed, the color of which is represented by an L value of up to 22, an a value of up to 7, and a b value of up to 9, wherein the polymer composition is obtained by combining a lignin-based filler with the polymer, the color of which is represented by an L value of 25-50, an a value of 7-15, and a b value of 11-22, wherein the polymer composition contains 0.5-50% by weight of lignin-based filler based on the total weight of the polymer composition, and the lignin-based filler is prepared by hydrothermal carbonization of lignin.
[0012] Based on the total weight of the polymer composition, the polymer composition may contain a total amount of 99.5-40% by weight, or 99-45% by weight, or 95-50% by weight of polymer.
[0013] Therefore, the color of lignin-based fillers can vary from brown to black. The inventors unexpectedly discovered that brown lignin-based fillers could be used to produce black polymer compositions.
[0014] The L, a, and b values represent the color values of the lignin-based filler or polymer composition, respectively. These values can be determined according to DIN EN ISO / CIE 11664-1:2020-03. They can be measured using any device capable of measuring the CIELab color space. Using lignin-based fillers may result in black polymer compositions. The polymer composition has the added benefit of eliminating the need for additional colorants or pigments to achieve the desired color.
[0015] The polymer composition may be a thermoplastic composition or an elastomer composition.
[0016] Thermoplastic compositions, also known as thermo-softening plastic compositions, are plastic polymer materials that become flexible or moldable at certain high temperatures and solidify upon cooling.
[0017] An elastomer (or rubber, as the term can be used interchangeably) is an elastic material that returns to its original shape when deformed. Rubber and elastomers generally refer to any material with rubber-like properties. Elastomer is short for elastic polymer. Elastomers are viscoelastic, meaning they are sticky, highly elastic polymers (plastics).
[0018] In one embodiment, the amount of lignin-based filler is 0.5-50% by weight, or 1-40% by weight, or 2-35% by weight, or 3-30% by weight, or 5-18% by weight, or 7-15% by weight, or 8-12% by weight, or about 10% by weight.
[0019] In one embodiment, the polymer composition is a thermoplastic composition, and the amount of lignin-based filler is 0.5-10% by weight, or 1-8% by weight, or 2-7% by weight, or 3-5% by weight, based on the total weight of the thermoplastic composition. In another embodiment, the polymer composition is an elastomer composition, and the amount of lignin-based filler is 10-50% by weight, or 12-40% by weight, or 15-35% by weight, or 18-30% by weight, based on the total weight of the elastomer composition.
[0020] Unless otherwise stated, “total weight” in this specification shall be understood as the weight of all components of the polymer composition, including possible moisture.
[0021] The color of lignin-based fillers can be represented by L values of 25–50, 27–45, 30–40, or 34–38. The color of lignin-based fillers can be represented by a value of 7–15, 7.5–13, 8–11, or 8.5–10. The color of lignin-based fillers can be represented by b values of 11–22, 13–20, 15–18, or 15.5–16.5.
[0022] The color of lignin-based fillers can be expressed using L values of 25–50, 27–45, 30–40, or 34–38; a values of 7–15, 7.5–13, 8–11, or 8.5–10; and b values of 11–22, 13–20, 15–18, or 15.5–16.5.
[0023] The color of the polymer composition can be represented by an L value of up to 20, or up to 18, or up to 15, or up to 10. The color of the polymer composition can be represented by an a value of up to 6.7, or up to 6.5, or up to 6. The color of the polymer composition can be represented by a b value of up to 8.7, or up to 8.5, or up to 8.
[0024] The color of the polymer composition may be represented by an L value of up to 22, or up to 20, or up to 18, or up to 15, or up to 10; an a value of up to 7, or up to 6.7, or up to 6.5, or up to 6; and a b value of up to 9, or up to 8.7, or up to 8.5, or up to 8.
[0025] The color of the polymer composition can be represented by an L value of at least 0. The color of the polymer composition can be represented by an a value of at least -50, or at least -30, or at least -10. The color of the polymer composition can be represented by a b value of at least -50, or at least -30, or at least -10.
[0026] The color of the polymer composition can be represented by an L value of at least 0; an a value of at least -50, or at least -30, or at least -10; and a b value of at least -50, or at least -30, or at least -10.
[0027] The lignin-based filler is prepared by hydrothermal carbonization (HTC) of lignin. In one embodiment, the lignin-based filler comprises or is composed of hydrothermally carbonized lignin.
[0028] Therefore, the filler used in the manufacture of polymer compositions is a lignin-based filler prepared by hydrothermal carbonization (HTC) of lignin. Hydrothermal carbonization of lignin refers to the thermochemical conversion process of lignin-containing materials in an aqueous suspension. Hydrothermal carbonization of lignin can prepare lignin derivatives with high carbon content and functional groups.
[0029] Lignin is a biopolymer and a key structural material for supporting tissues in most living plants. It is a renewable material that can be used in a variety of applications.
[0030] Lignin can be derived from any suitable source. Lignin can be derived from, for example, wood, such as hardwood, softwood, broadleaf wood, or combinations thereof, or from any other biomass, such as sugarcane. Wood can be derived from, for example, pine, poplar, beech, aspen, spruce, eucalyptus, ash, or birch. Wood can also be any combination or mixture of these woods.
[0031] In one embodiment, the lignin-based filler is prepared from lignin derived from an enzymatic hydrolysis process and / or a sulfate process and subjected to hydrothermal carbonization. In another embodiment, the lignin-based filler is prepared from lignin derived from an enzymatic hydrolysis process and subjected to hydrothermal carbonization. In yet another embodiment, the lignin-based filler is prepared from lignin derived from a sulfate process and subjected to hydrothermal carbonization.
[0032] In one embodiment, the enzymatic hydrolysis process includes the enzymatic hydrolysis of a plant-based feed (e.g., a wood-based feed). Prior to enzymatic hydrolysis, the wood-based feed may have undergone a pretreatment process, including impregnation and partial hydrolysis. The pretreatment process may provide cellulose from the wood-based feed, which can then be hydrolyzed during the enzymatic hydrolysis process.
[0033] In one embodiment, the enzymatic hydrolysis process includes the enzymatic hydrolysis of cellulose. In one embodiment, the lignin-based filler is prepared from lignin derived from wood pulping, such as sulfate lignin.
[0034] Lignin-based fillers can be prepared as follows. The lignin used can be derived from processes that produce lignin, for example, through enzymatic hydrolysis of lignocellulose feed, or from lignin derived from sulfate processes. Other lignin sources can also be used.
[0035] In one embodiment, the starting material used to prepare the lignin-based filler is lignin derived from an enzymatic hydrolysis process. Enzymatic hydrolysis is a process in which enzymes assist in the cleavage of bonds in a molecule by adding water. In one embodiment, the enzymatic hydrolysis includes the enzymatic hydrolysis of cellulose. In one embodiment, the lignin-based filler is prepared from lignin derived from an enzymatic hydrolysis process and subjected to hydrothermal carbonization.
[0036] The inventors surprisingly discovered that when lignin-based fillers are prepared, for example, using lignin from an enzymatic hydrolysis process, the ash content of the lignin-based fillers can be reduced. The lower ash content has additional benefits, such as higher purity of the lignin-based fillers.
[0037] Lignin can be derived from second-generation (2G) biomass. Second-generation (2G) biomass can be understood as non-edible and non-food biomass. In contrast to the term second-generation biomass, first-generation biomass should be considered edible biomass.
[0038] The derived lignin is soluble in alkaline solutions, such as NaOH. Dissolution can be achieved by heating the mixture of lignin and alkaline solution to approximately 80°C, adjusting the pH to above 7, for example, a value of 9-11, and mixing the mixture for a predetermined time. The mixing time can last approximately 2-3 hours. The exact pH value is determined based on the target grade of the product.
[0039] The dissolved lignin can then be subjected to hydrothermal carbonization (HTC).
[0040] Hydrothermal carbonization can be carried out in a reactor (HTC reactor), or, if desired, in batches in several parallel reactors. The dissolved lignin can be preheated before entering the HTC reactor. The temperature in the HTC reactor can be 150-250°C, and the pressure can be 20-30 bar. The residence time in the HTC reactor can be approximately three to six hours. In the HTC reactor, the lignin is carbonized, thereby precipitating stabilized lignin derivatives with a high specific surface area. The resulting slurry containing carbonized lignin can then be removed and cooled.
[0041] Therefore, a slurry containing lignin-based fillers was formed.
[0042] Slurry containing lignin-based filler can be fed into a separation unit, where precipitated lignin can be separated from the slurry. The separated lignin-based filler can be dried and recycled. If necessary, the lignin-based filler can be washed before drying. The recycled lignin-based filler can be further processed before being used as lignin-based filler, such as crushing, further drying, grinding, etc. The resulting lignin-based filler is a renewable bio-based filler.
[0043] In the process described above, lignin polymers are interconnected. Therefore, lignin-based packing materials can be considered to contain or consist of interconnected lignin polymers. The interconnected or linked lignin polymers may no longer be soluble. However, the smaller lignin polymer chains remain soluble and can therefore be used with standard analytical techniques, such as size exclusion chromatography or nuclear magnetic resonance spectroscopy (NMR), which require the analyte to be dissolved in a solvent. Thus, the different properties of the soluble fractions in lignin-based packing materials can be determined.
[0044] In one embodiment, the lignin-based filler comprises 0.1-3% by weight, or 0.1-2.5% by weight, or 0.2-2.0% by weight, or 0.3-1.5% by weight, or 0.4-1.0% by weight of ash. The ash content is determined according to DIN 51719.
[0045] The inventors surprisingly discovered that when lignin-based fillers are prepared, for example, using lignin from an enzymatic hydrolysis process, the ash content of the lignin-based fillers can be reduced. The lower ash content has additional benefits, such as higher purity of the lignin-based fillers.
[0046] Lignin-based fillers may contain a total of 62-70% by weight, or 63-69% by weight, or 64-68% by weight of carbon. The carbon content in lignin-based fillers may be determined according to DIN 51732 (1997).
[0047] In one embodiment, the solubility of the lignin-based filler in 0.1 M NaOH is 1-40% by weight, or 3-35% by weight, or 5-30% by weight. Solubility can be measured as follows: First, the sample is dried at 60°C for four hours. 0.5 g of the sample is weighed and suspended in 50 ml of 1% 0.1 M NaOH at 22°C. Mixing continues for 1 hour, then the sample is placed on glass microfiber paper (1.6 μm), and the filter paper with the sample is dried at 60°C for 2 hours. The dissolved portion of the sample can be determined by gravimetric analysis.
[0048] In one embodiment, when determined based on the soluble fraction of the lignin-based filler, the weight-average molecular weight (Mw) of the lignin-based filler is 1000-4000 Da, or 1300-3700 Da, or 1700-3200 Da, or 2500-3000 Da, or 2600-2900 Da, or 2650-2850 Da. The weight-average molecular weight can be determined by size exclusion chromatography (SEC) using 0.1 M NaOH as the eluent, with a sample volume of approximately 1 mg / ml dissolved in 0.1 M NaOH. The molecular weight is measured based on a polystyrene sulfonate standard. A UV detector with a wavelength of 280 nm is used.
[0049] When determined based on the soluble fraction of lignin-based fillers, the polydispersity index (PDI) of the lignin-based fillers can be 1.5–5.0, or 1.8–4.5, or 1.9–4.3, or 2.1–4.0, or 2.4–3.5, or 2.6–3.2. The polydispersity index can be determined by size exclusion chromatography (SEC). PDI is a measure of the distribution of molecular weights in a given polymer sample. PDI is calculated by dividing the weight-average molecular weight (Mw) by the number-average molecular weight (Mn). PDI represents the distribution of several individual molecular weights in a polymer batch.
[0050] The STSA value of lignin-based fillers can be 3-150 m. 2 / g, or 5-100 m 2 / g, or 7-60 m 2 / g. STSA values can be determined according to ASTM D6556 standard.
[0051] In one embodiment, the density of the lignin-based filler is at most 1.5 g / cm³. 3In one embodiment, the density of the lignin-based filler is 1.0-1.5 g / cm³. 3 Or 1.15-1.35 g / cm³ 3 or 1.1-1.4 g / cm³ 3 Density can be determined according to ISO 21687 standard.
[0052] In one embodiment, the polymer composition is a thermoplastic composition comprising at least one polymer selected from polyethylene, polypropylene, polystyrene, ethylene vinyl acetate (EVA), polybutylene terephthalate (PBAT), polyamide, polyacrylate, polyester, acrylonitrile-butadiene-styrene (ABS), polycarbonate, polylactic acid (PLA), and polyvinyl chloride (PVC). In one embodiment, the thermoplastic composition comprises polyethylene, polypropylene, and / or acrylonitrile-butadiene-styrene. That is, a thermoplastic composition can be produced using one type of polymer, or a combination of two or more different polymers can be used to produce the thermoplastic composition.
[0053] In one embodiment, the polymer composition is an elastomer composition comprising at least one polymer selected from ethylene propylene diene monomer (EPDM), ethylene propylene rubber (EPR), butadiene rubber (BR), chloroprene rubber (CR), chlorohydrin rubber (ECO), epoxidized natural rubber (ENR), nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), butyl rubber (IIR), isoprene rubber (IR), α-methylstyrene-butadiene rubber (MSBR), natural rubber (NR), styrene-butadiene rubber (SBR), brominated butyl rubber (BIIR), and chlorinated butyl rubber (CIIR). That is, the elastomer composition can be produced using one type of polymer, or it can be produced using a combination of two or more different polymers.
[0054] The polymers used in the polymer composition may be derived from fossil sources. At least one polymer may be derived from a bio-based source. At least one polymer may be derived from either a fossil source or a bio-based source. All polymers used in the polymer composition may be derived from either a fossil source or a bio-based source. Alternatively, polymers derived from both fossil and bio-based sources may be used in the polymer composition. Moreover, a mixture of polymers derived from both fossil and bio-based sources may be used in the polymer composition.
[0055] The polymer composition can be prepared using at least one polymer and a lignin-based filler. Other components or materials, such as plasticizers, additives, lubricants, stabilizers, antioxidants, curing agents, foaming agents, etc., can also be used to prepare the polymer composition. In one embodiment, combining at least one polymer and filler further includes combining one or more plasticizers, additives, lubricants, stabilizers, antioxidants, curing agents and / or foaming agents to form the polymer composition.
[0056] When preparing polymer compositions, a so-called masterbatch can first be prepared using at least one polymer and filler. Masterbatches can be prepared by mixing the polymer and filler at high temperatures. Furthermore, depending on the requirements, the masterbatch may also contain other plasticizers, additives, lubricants, stabilizers, antioxidants, curing agents, foaming agents, etc. Masterbatches are generally considered solid products (typically plastics, rubbers, or elastomers) in which pigments or fillers are optimally dispersed in a carrier material at high concentrations. The carrier material is compatible with the main polymer to be incorporated during molding, thereby allowing the final plastic product (i.e., the polymer composition) to acquire color or properties from the masterbatch.
[0057] Alternatively, the polymer composition can be directly formulated from the polymer and filler at elevated temperatures. Furthermore, other additives, lubricants, stabilizers, antioxidants, curing agents, foaming agents, etc., can be directly formulated with the polymer and filler as needed.
[0058] The temperature used when combining at least one polymer with a filler can vary depending on the type of polymer used. The appropriate temperature for each polymer is readily apparent to those skilled in the art. Furthermore, polymer suppliers define suitable processing temperatures for different polymers. Generally, usable temperatures are, for example, 20–350°C, or 40–330°C, or 70–300°C, or 120–280°C, or 150–250°C.
[0059] After mixing at least one polymer with a filler, the polymer composition can be further cured at high temperature in a subsequent step.
[0060] Polymer compositions can be either non-expanded or expanded. When a polymer composition expands, it can take the form of foam. Expanded polymer compositions can be formed by introducing air or a gas (e.g., CO2) into the polymer composition during the preparation process. For example, a foaming agent can be used to expand the polymer composition to make it foam. Polymer foaming is the process of introducing gas-filled units, bubbles, into the material structure. By foaming, the density of the material can be reduced with less material consumption. Furthermore, the density of the foam can be controlled, and various densities can be produced according to product requirements. This reduces weight and material costs. Expanded polymer compositions may also be referred to as foamed polymer compositions or polymer foams.
[0061] The polymer composition can be further processed into articles by extrusion, injection molding, compression molding, blow molding, injection blow molding, injection stretch blow molding, thermoforming, vacuum forming, melt spinning, electrospinning, melt blow molding, blown film, film casting, extrusion coating, rotational molding, co-extrusion, lamination, calendering, melt deposition modeling, or any combination thereof.
[0062] The total organic carbon content of the polymer composition produced, as determined by DIN EN 15936:2012-11, may be 90–100%, 93–99%, or 96–98%. The term “total organic carbon (TOC)” can be understood as the carbon content in the organic compounds or, in this case, in the polymer composition.
[0063] According to DIN 51719:1997-07, the produced polymer composition may contain 0.1–7.5%, or 0.3–7.0%, or 0.5–6%, or 1.0–5.0%, or 1.5–3.0% ash in total.
[0064] The amount of renewable materials in the produced polymer composition can be 5-100%, 10-95%, 15-90%, or 20-85%.
[0065] In one embodiment, the polymer composition does not include any colorants other than lignin-based fillers.
[0066] The use of lignin-based fillers as defined in this specification has the additional utility of providing black polymer compositions without the need for any other coloring agents. The use of lignin-based fillers has the added utility of being a biological material, thus allowing the production of polymer compositions with reduced fossil-based components. The use of lignin-based fillers also has the additional utility of increasing the total biomass carbon content in the polymer composition. Biomass carbon refers to carbon stored in biological materials such as plants or soil. Carbon accumulates in plants through photosynthesis, therefore bio-based products may help reduce atmospheric carbon dioxide levels.
[0067] Example
[0068] The embodiments of this disclosure will now be described in detail.
[0069] The following description discloses some embodiments in such detail to enable those skilled in the art to utilize methods based on this disclosure. Not all steps of the embodiments are discussed in detail, as many steps will be apparent to those skilled in the art based on this disclosure.
[0070] Example 1 – Production of Polymer Compositions Using Lignin-Based Fillers
[0071] In this embodiment, different polymer compositions were produced. The aim was to evaluate the properties and color of the polymer compositions produced using different amounts of renewable lignin-based filler (LBF). Comparative examples were prepared by not using lignin-based filler in the polymer compositions.
[0072] According to the above description in this manual, lignin-based fillers are prepared by using lignin material obtained from beech wood-based feed through an enzymatic hydrolysis process and then undergoing hydrothermal carbonization treatment.
[0073] Thermoplastic and elastomer compositions were produced and tested.
[0074] This thermoplastic composition is prepared by mixing lignin-based fillers and thermoplastic polymers, along with components such as calcium stearate (lubricant), Irganox 1010 antioxidant, and polyethylene wax (lubricant). First, a masterbatch is formed containing 40% by weight of lignin-based filler, 52% by weight of polymer, and a total of 8% by weight of an additive package (consisting of 2% calcium stearate (lubricant), 2% Irganox 1010 antioxidant, and 4% polyethylene wax (lubricant)). This is then further mixed with other polymers to achieve 1%, 3%, or 5% by weight of lignin-based filler content.
[0075] The masterbatch is formed into granules, and its preparation is as follows:
[0076] The samples were compounded using a Leistritz ZSE 27 MAXX high-speed co-rotating twin-screw extruder with a screw diameter of 27 mm and an L / D ratio of 48. It includes atmospheric and vacuum degassing ports, a side feeder for filler, and can be equipped with a melt pump and a gas injection unit for foaming. The unit is equipped with a Gala PLU underwater granulation system to granulate the extruded material into pellets.
[0077] The masterbatch granules are then mixed with polymer granules (without any other additives) to produce flat plates, which are then tested. Flat plates are prepared by injection molding samples onto an ARBURG 420 M allrounder 1000-350. This machine is equipped with quick-change molds for ISO-certified test samples.
[0078] In the comparative example of pure polymer, the plate was formed directly from polymer particles.
[0079] The elastomer composition was prepared as follows: In the first mixing step, lignin-based filler (115 phr), polymer (EPDM, Keltan 4465, 150 phr), processing oil (Tudaen 1924, 25 phr), polyethylene glycol (PEG4000, 2 phr), stearic acid (2 phr), and zinc oxide (5 phr) were mixed for 6.25 minutes using a laboratory kneader (ERMAFA interlocking internal mixer TMI 0,6) to form a base mixture. In the second mixing stage, accelerator (MBT 1 phr, ZDTP 2 phr, TBzTD 1.05 phr) and sulfur (1.5 phr) were added to the base mixture, and all substances were mixed for a total of four minutes. The mixture was then pressed into sheets and cured at 170°C for 13 minutes in a MonTech Werkstoffprüfmaschinen GmbH LP3000 600kN hydraulic press.
[0080] The color of the lignin-based filler and the prepared polymer composition was measured according to standard DIN EN ISO / CIE 11664-1:2020-03. The results are shown in Table 1 below:
[0081]
[0082] The results above show that when brown-shaded lignin-based fillers are used, black polymer compositions can be produced.
[0083] It will be apparent to those skilled in the art that, with the development of technology, the basic idea can be implemented in various ways. Therefore, the implementation methods are not limited to the embodiments described above; rather, they can vary within the scope of the claims.
[0084] The embodiments described above can be used in any combination with each other. Several embodiments can be combined together to form further embodiments. The uses and polymer compositions disclosed herein may include at least one of the foregoing embodiments. It is understood that the above benefits and advantages may apply to one embodiment or several embodiments. The embodiments of the present invention are not limited to embodiments that solve any or all of the described problems, nor are they limited to embodiments that have any or all of the described benefits and advantages. It should be further understood that the reference to "a" item means one or more of the items. The term "comprising" as used in this specification includes the feature or behavior that follows, without excluding the presence of one or more other features or behaviors.
Claims
1. Use of lignin-based filler in the production of polymer compositions, wherein the color of the lignin-based filler is represented by an L value of 25–50, an a value of 7–15, and a b value of 11–22, and the color of the polymer composition is represented by an L value of up to 22, an a value of up to 7, and a b value of up to 9, wherein the amount of lignin-based filler used is 0.5–50% by weight based on the total weight of the polymer composition, wherein the lignin-based filler is prepared by hydrothermal carbonization of lignin.
2. The use as described in claim 1, wherein, The polymer composition is a thermoplastic composition or an elastomer composition.
3. The use as described in any of the preceding claims, wherein, The polymer composition is a thermoplastic composition, and the amount of lignin-based filler is 0.5-10% by weight, or 1-8% by weight, or 2-7% by weight, or 3-5% by weight, based on the total weight of the thermoplastic composition.
4. The use as described in any of the preceding claims, wherein, The polymer composition is an elastomer composition, and the amount of lignin-based filler is 10-50% by weight, or 12-40% by weight, or 15-35% by weight, or 18-30% by weight, based on the total weight of the elastomer composition.
5. The use as described in any of the preceding claims, wherein, The color of the lignin-based filler is represented by an L value of 27–45, or 30–40, or 34–38.
6. The use as described in any of the preceding claims, wherein, The color of the lignin-based filler is represented by an a value of 7.5 – 13, or 8 – 11, or 8.5 – 10.
7. The use as described in any of the preceding claims, wherein, The color of the lignin-based filler is represented by a b value of 13–20, or 15–18, or 15.5–16.
5.
8. The use as described in any of the preceding claims, wherein, The color of the polymer composition is represented by an L value of up to 20, or up to 18, or up to 15, or up to 10.
9. The use as described in any of the preceding claims, wherein, The color of the polymer composition is represented by an a value of up to 6.7, or up to 6.5, or up to 6.
10. The use as described in any of the preceding claims, wherein, The color of the polymer composition is represented by a b value of up to 8.7, or up to 8.5, or up to 8.
11. The use as described in any of the preceding claims, wherein, The lignin-based filler is prepared by hydrothermal carbonization of lignin.
12. The use as described in any of the preceding claims, wherein, The polymer composition is a thermoplastic composition comprising at least one polymer selected from polyethylene, polypropylene, polystyrene, ethylene vinyl acetate (EVA), polybutylene terephthalate (PBAT), polyamide, polyacrylate, polyester, acrylonitrile-butadiene-styrene (ABS), polycarbonate, polylactic acid (PLA), and polyvinyl chloride (PVC).
13. The use as described in any of the preceding claims, wherein, The polymer composition is an elastomer composition comprising at least one polymer selected from ethylene propylene diene monomer (EPDM), ethylene propylene rubber (EPR), butadiene rubber (BR), chloroprene rubber (CR), chlorohydrin rubber (ECO), epoxidized natural rubber (ENR), nitrile butadiene rubber (NBR), hydrogenated nitrile butadiene rubber (HNBR), butyl rubber (IIR), isoprene rubber (IR), α-methylstyrene-butadiene rubber (MSBR), natural rubber (NR), styrene-butadiene rubber (SBR), brominated butyl rubber (BIIR), and chlorinated butyl rubber (CIIR).
14. The use as described in any of the preceding claims, wherein, The polymer used in the polymer composition is derived from fossil sources.
15. The use as described in any of the preceding claims, wherein, At least one polymer is derived from a bio-based source.
16. Use of the polymer composition produced by any one of claims 1-15 in packaging applications, automotive applications, construction applications, agricultural applications and / or electronic applications.
17. The polymer composition produced by any one of claims 1-15 is used in tires, tire treads, tire sidewalls, cable sheaths, hoses, drive belts, conveyor belts, roller covers, shoe soles, shock absorbers, seals, profiles and / or damping elements.
18. A polymer composition wherein the color is represented by an L value of up to 22, an a value of up to 7, and a b value of up to 9, wherein, The polymer composition is obtained by combining a lignin-based filler with a polymer, the color of which is represented by an L value of 25-50, an a value of 7-15, and a b value of 11-22, wherein the polymer composition contains 0.5-50% by weight of the lignin-based filler based on the total weight of the polymer composition, and the lignin-based filler is prepared by hydrothermal carbonization of lignin.